The opinion of European Union on human stem cell research and use [Avrupa birliǧi'nin i̇nsan kök hücresi araştirmalari ve kullanimi hakkindaki görüşü] - (:unkn) unknown (My University, 2004)
The use of human stem cells is controversial today, since human embryos and fetal cadavers seem to be the main source of them. Currently many local and national ethic committees and authorities are handling ethical issues raised by the embryo researches. A 'Working Group' on Ethics in Science and New Technologies established within the European Council has brought an official opinion into attention of public in November 2000. The expert opinion text presents current situation in stem cell and embryo researches. Underlining the main interests raised by stem cell research, the text starts to review the legal statue in the member states of European Union (EU), and then lists the main ethical concerns about the subject. According to the opinion declared, the Working Group emphasizes the fundamental ethical principles already recognised in its former declarations. The Group reminds EU's pluralistic principles, and presents different approaches based on diverse cultures as the basic units of ethical awareness of European society. Having respect for the legal and ethical decisions taken by the member countries, the Group makes clear, that the research using embryonic stem cells in order to develop new treatments for variable diseases, is not to be prohibited, provided that it was conducted according a number of requirements.